Patient-safety culture among emergency and critical Care Nurses in a Maternal and Child Department - Fuseini, Abdul-Karim Jebuni (2023)
Introduction: The quality of healthcare has multiple dimensions, but the issue of patient safety stands out due to the impact it has on health outcomes, particularly on the achievement of the Sustainable Development Goals (SDGs), expressly SDG3. In the services that we propose to study, the patient-safety culture had never been evaluated. Aim: To evaluate nurses’ perceptions of the patient-safety culture in the Emergency and Critical Care Services of the Maternal and Child Department of a University Hospital and to identify strengths, vulnerabilities, and opportunities for improvement. Methods: This an exploratory, cross-sectional study with a quantitative approach, using the Hospital Survey on Patient Safety Culture as an instrument for data collection. The population were all nurses working in the emergency and critical care services of the maternal and child-health department, constituted, at the time of writing, by 184 nurses, with a response rate of 45.7%. Results: Applying the guidelines from the Agency for Healthcare Research and Quality (AHRQ), only teamwork within units had a score greater than 75%. For this reason, it is considered the strength (fortress) in the study. The lowest-rated were non-punitive responses to errors and open communication. Conclusion: The overall average percentage score is below the benchmark of the AHRQ, indicating that issue of patient safety is not considered a high priority, or that the best strategies to make it visible have not yet been found. One of the important implications of this study is the opportunity to carry out a deep reflection, within the organization, that allows the development of a non-punitive work environment that is open to dialogue, and that allows the provision of safe nursing care.